Investigation of Rare Non-Coding Variants in Familial Multiple Myeloma - Niazi, Yasmeen; Paramasivam, Nagarajan; Blocka, Joanna; Kumar, Abhishek; Huhn, Stefanie; Schlesner, Matthias; Weinhold, Niels; Sijmons, Rolf; De Jong, Mirjam; Durie, Brian; Goldschmidt, Hartmut; Hemminki, Kari; et al. (Cells, 2022)
Multiple myeloma (MM) is a plasma cell malignancy whereby a single clone of plasma cells over-propagates in the bone marrow, resulting in the increased production of monoclonal immunoglobulin. While the complex genetic architecture of MM is well characterized, much less is known about germline variants predisposing to MM. Genome-wide sequencing approaches in MM families have started to identify rare high-penetrance coding risk alleles. In addition, genome-wide association studies have discovered several common low-penetrance risk alleles, which are mainly located in the non-coding genome. Here, we further explored the genetic basis in familial MM within the non-coding genome in whole-genome sequencing data. We prioritized and characterized 150 upstream, 5' untranslated region (UTR) and 3' UTR variants from 14 MM families, including 20 top-scoring variants. These variants confirmed previously implicated biological pathways in MM development. Most importantly, protein network and pathway enrichment analyses also identified 10 genes involved in mitogen-activated protein kinase (MAPK) signaling pathways, which have previously been established as important MM pathways.
Keywords: MAPK pathway; Multiple Myeloma; celogenomová asociační studie; mnohočetný myelom; zárodečné mutace; sekvenování celého genomu; Genome-Wide Association Study; MAP Kinase Signaling System; whole-genome sequencing; Whole Genome Sequencing; Humans; Germ-Line Mutation; familial multiple myeloma; non-coding genome; lidé; MAP kinasový signální systém